2006
DOI: 10.2527/jas.2005-632
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the amount of n-3 fatty acid in meat from young Holstein bulls through nutrition1

Abstract: Fifty-four Holstein bulls were blocked by initial BW (301 +/- 7.4 kg) and randomly assigned to 6 treatments following a 3 x 2 factorial arrangement, with 3 concentrate lipid levels (5, 8, and 11% of DM) and 2 lipid sources (whole canola seed and whole linseed), with the objective of evaluating the possibility of increasing the content of n-3 fatty acids in meat. Concentrates (mostly corn meal) were isonitrogenous and isocaloric. Concentrate and straw were both fed ad libitum. Animal BW was recorded every 2 wk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
50
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 33 publications
9
50
4
Order By: Relevance
“…The low roughage intake registered in heifers fed FCH is in agreement with data reported by Iraira et al (2012), who recorded an average proportion of 96% and 4% of concentrate and barley straw respectively, when they used this feeding method in Simmental heifers fed a concentrate diet from 115 to 185 kg of BW. This contrasts, however, with data obtained by other authors (Mach et al, 2006;Robles et al, 2007;González et al, 2008) who also worked in the finishing period and fed animals with concentrate and barley straw, both offered separately and ad libitum. These latter studies reported proportions of concentrate in the diet ranging from 86 to 88%, and proportions of barley straw ranging from 14 to 12%.…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…The low roughage intake registered in heifers fed FCH is in agreement with data reported by Iraira et al (2012), who recorded an average proportion of 96% and 4% of concentrate and barley straw respectively, when they used this feeding method in Simmental heifers fed a concentrate diet from 115 to 185 kg of BW. This contrasts, however, with data obtained by other authors (Mach et al, 2006;Robles et al, 2007;González et al, 2008) who also worked in the finishing period and fed animals with concentrate and barley straw, both offered separately and ad libitum. These latter studies reported proportions of concentrate in the diet ranging from 86 to 88%, and proportions of barley straw ranging from 14 to 12%.…”
contrasting
confidence: 55%
“…Carcasses classified according to the EU classification system were close to values recorded by FEDNA (2008) for Simmental heifers. The final pH (5.6 on average) was in the interval considered to be normal (between 5.4 to 5.8) for beef (Mach et al, 2006). These values suggest that there was no increased stress before slaughter, because the acidification of the muscle occurred as expected.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Samples of 200 g gluteus medius muscle were collected immediately after slaughter for meat analyses carried out at the Centre of Meat Technology (CTC-IRTA). Analyses of gluteus medius lipid components included the determination of percentage of IMF, cholesterol content and fatty acid composition (in the C12 to C22 interval) were performed as follows: IMF content was determined by Near Infrared Transmittance (NIT; Infratec R 1625, Tecator AB, Hoganas, Sweden) , Pinhu et al, 2008 fatty acid composition was analysed by gas chromatography of methyl esters as described in (Mach et al, 2006), and cholesterol content was measured following (Cayuela et al, 2003). The most relevant phenotypic traits analysed in this study, along with their abbreviations and statistics in the studied Duroc population, are shown in Table 1 (complete data set was finally obtained from 338 animals).…”
Section: Methodsmentioning
confidence: 99%
“…Due to ruminal biohydrogenation, the proportion of 18:3 n-3 in percentage of total FA remains low. For example in Longissimus thoracis, it increases from 0.5 to 0.9-1.6% (Normand et al, 2005, 5 trials), from 0.4 to 1.9% (Mach et al, 2006), from 0.4 to 0.8% (Barton et al, 2007), from 0.6 to 2.0% (Herdmann et al, 2010), from 1.2 to 1.6% (Corazzin et al, 2012), from 0.4 to 0.6% (Habeanu et al, 2014), from 0.9 to 1.4% (Mialon et al, 2015). Differences in the extent of the increase depend more on the amount of added fat and their processing than on the duration of distribution before slaughter.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%